[PP.23.22] CORRELATION CENTRAL BLOOD PRESSURE RESPONSE WITH CREATININ, EGFR AND HEART RATE AFTER RENAL DENERVATION IN PATIENTS WITH RESISTANT HYPERTENSION IN UKRAINE. (September 2016) - Rekovets, O.; Sirenko, Y.; Dobrokhod, A.; Torbas, O.; Kushnir, S.; Primak, G.; Vaschylko, A.; Sidorenko, P.; Polischuk, S.; Granich, V.
Abstract : Objective: The purpose of this analysis was to determine which correlations relationships were associated with renal denervation efficacy in a cohort of 8 patients. Design and method: We screened 436 subjects selected 8 patients (1, 8%) (5 male, 3 female) with true resistant hypertension for renal denervation (RDN) by Simplicity catheter (Medtronic). Mean age 52, 1 ± 3, 8 years. At baseline office blood pressure (BP) was 156, 9/95, 0 ± 2, 9/2, 1 mmHg. Patient took in average 5 drugs. Mean baseline 24ABPM was 151, 4 ± 4, 8/82, 6 ± 4, 8 mmHg, 24HR was 65, 3 ± 2, 7 b.p.m. Results: Mean follow-up was 2, 3 ± 0, 3 years. 1 month after RDN office SBP decreased by 8, 0 ± 4, 3 mmHg, cBP −21, 1 ± 6, 4 mmHg and 24SBP decreased by 7, 7 ± 4, 7 mmHg. 2 years after RDN office SBP decreased by 29, 1 ± 6, 8 mmHg, cSBP decreased by 7, 6 ± 5, 6 mmHg and 24SBP decreased by 13, 3 ± 4, 6 mmHg. cBP after 1 month correlated with decreased delta office HR 1 month (R = −0, 768; P = 0, 001), cBP after 6 month correlated with delta office HR 1 month, (R = −0, 700; P = 0, 024); delta office HR 6 month (R = −0, 989; P = 0, 001) delta office HR 2 years (R = −0, 800; P = 0, 005). Decreased cBP after 2 years was associated with less decreased HR24 (ABMP) after 1 month (R = −0, 975; P = 0, 001) and with less decreased HR24 (ABMP) after 2 years (R = -0, 800; P = 0, 017). eGFR after 1 month RDN direct correlated with delta office HR 7 days (R = 0, 800; P = 0, 017); with delta office HR 6 month (R = 0, 998; P = 0, 001); with delta office HR 2 years (R = 0, 800; P = 0, 017). Creatinin after 6 month correlated with delta office HR 7 days (R = −0, 866; P = 0, 026). Creating after 2 years correlated with delta office HR 1 month (R = −0, 800; P = 0, 017). If office HR was not decreased after 7 days, 1 month, it was associated with higher creating 6 month and 2 years after RDN. Conclusions: Poor decreased office HR after RDN 7 days, 1 month, 6 month or 2 years it was associated with less decreased central BP after 1, 6 month, increased creatinin after 6 month and 2 years; and associated with decreased eGFR 7 days and 1 month after RDN. Less decreased central BP after 2 years was associated with less decreased HR (ABMP) after 1 month, 2 years RDN.